1950
DOI: 10.1001/archneurpsyc.1950.02310210003001
|View full text |Cite
|
Sign up to set email alerts
|

Results of Spinal Pyramidotomy in the Treatment of the Parkinsonian Syndrome

Abstract: THE NEED for a method affording relief through surgical measures to patients suffering from severe parkinsonism can scarcely be questioned by anyone who has had to do with this unhappy group. The use of drugs of the belladonna series should, of course, always be tried, and if it is satisfactory surgical intervention need scarcely be considered; but failures are numerous, and, all in all, the medical profession has little reason to be complacent over the results so far obtained. It has been clearly shown by sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1953
1953
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Unfortunately the question is not at all academic because, lacking better information, surgeons have chiefly attempted to control hyperkinetic disorders by the only scheme in sight (namely, resection of portions of the pyramidal system (1, 2)), thus substituting paralysis for tremor. In some of the patients undergoing cortical extirpation seizures developed postoperatively; Putnam (3) mentions, in addition, aphasia. Putnam's method of sectioning pyramidal fibers in the cervical cord was said to permit a later return of motor power, but Browder (19) has reported that tremor also returns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately the question is not at all academic because, lacking better information, surgeons have chiefly attempted to control hyperkinetic disorders by the only scheme in sight (namely, resection of portions of the pyramidal system (1, 2)), thus substituting paralysis for tremor. In some of the patients undergoing cortical extirpation seizures developed postoperatively; Putnam (3) mentions, in addition, aphasia. Putnam's method of sectioning pyramidal fibers in the cervical cord was said to permit a later return of motor power, but Browder (19) has reported that tremor also returns.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention in parkinsonism has not been generally considered to offer much hope for solution of the problem (1). Hitherto it has mainly consisted of damaging the corticospinal (pyramidal) system, either at the motor cortex (1, 2) or in the cervical cord (3), and so producing a loss of motor power and some relief of tremor. As late as 1954, Merritt (4) asserted that surgical procedures “appear to have some degree of success only when the corticospinal tracts are injured and a hemiplegia or mild hemiparesis is substituted for the tremor or rigidity.”…”
mentioning
confidence: 99%
“…Other investigators attempted pedunculotomy, spinal cord sectioning, and lesioning of the internal capsule, all with high morbidity and inconsistent results (Table 1). 18–21 Gradually, the field moved away from the notion that sectioning motor fibers was beneficial in the treatment of tremor and hypokinetic or hyperkinetic movement disorders. The important lesson had been learned that by sectioning the pyramidal tract at any level, improvements in tremor did not extend beyond that expected from paralysis.…”
Section: History Of Stereotaxic Surgery: the Rise Fall Rise And Famentioning
confidence: 99%
“…Bucy and Case (2) and Klemme (3) lesioned the cortex and Browder (4) the internal capsule, while others such as Meyers (5), Spiegel et al (6) and Spiegel and Wycis (7), Fenelon (8), Guiot and Brion (9), and Cooper (10) made lesions in regions of the thalamus and basal ganglia. Still others destroyed portions of the peduncle (11) or spinal cord (12) or ablated the posterior nerve roots (13). Many patients died while others suffered serious morbidity; however, a few improved.…”
mentioning
confidence: 99%